SiC/GaN power semiconductor devices theoretical comparison and experimental evaluation - Li, Ke; Evans, Paul; Johnson, Christopher Mark (2016)
SiC and GaN power transistors conduction loss and switching losses are compared in this paper. In order to compare performance of the same power rating device, a theoretical analysis is given to compare SiC device conduction loss and switching losses change when device maximal blocking voltage reduces by half. Then static and dynamic characteristics of commercial SiC and GaN power transistors are compared and it is shown that GaN-HEMT would still have smaller ON-state resistance and inter-electrode capacitance in comparison with a 600V SiC device. After that, switching losses E8w of a GaN-HEMT is measured and compared with that of a 1200V SiC-JFET and a 600V SiC-MOSFET, in which it is shown that E8w of a GaN-HEMT is smaller than a SiC power transistor with the same power rating.